Coaching Marketing Management Technology for Crackers Small Industry in Ujung Pangkah Village, Gresik Regency - Cempena, I.B; Ratnawati, Tri; Aldo, Raden Wimendy; Oktaviyanto, Nanda (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
The potential of marine resources in the coastal area of Ujung Pangkah is a potential in the field of fisheries which can be a processing industry for various products but has limited production equipment, thus making the production volume unable to reach the expected target when there are many orders. Marketing still applies the conventional method, just waiting for the middleman to come to pick up the goods, so there is no effort to develop the market area. The objectives of coaching or mentoring appropriate marketing management technology for small cracker industry managers are: 1) Increase production capacity, 2) Improve production quality, 3) Save labor costs, 4) Save time in the production process, 5) Increase production cost efficiency, 6) Implementing digital marketing, 7) Lowering product selling prices, 8) Increasing sales, 9) Increasing operating profit, 10) Increasing business assets. The results in this study were the small cracker industry community in Ujung Pangkah Village, Gresik Regency, able to compete in online e-commerce sales, able to operate production equipment as needed to increase production volume. This research has limitations, so it is recommended for further service activities in Pangkah Kulon Village, Ujung Pangkah, Gresik Regency to promote the place for making processed fish crackers, with this promotion it will attract visitors to buy the cracker product so that it will be increasingly known by the wider community and foreign countries.